COVID-19 Pandemic's Economic Impact on the Healthcare Sector: a case study of Guaranda Basic Hospital (IESS) from 2020 to 2022 - Barragán Quizhpe, Christian Fernando (2023)
The COVID-19 pandemic has had a significant impact on the healthcare system worldwide, necessitating the reorganization of staff and the implementation of preventive measures to mitigate the spread of the virus. In this context, several studies have examined the clinical and financial impact of COVID-19 in different medical specialties and in different countries, approached from various perspectives. In this research, an efficiency analysis of Guaranda Basic Hospital (GBH) was conducted using data collected from 2020 to 2022. Information was obtained from official sources and analyzed using spreadsheets. The results showed continuous losses, with a negative profit margin and cost efficiency below optimal levels. The impact of the COVID-19 pandemic on the economy and healthcare systems was discussed. Solutions such as the implementation of digital health technology and the need to improve bed turnover, optimize resource management, and ensure adequate financing for sustainability were suggested.